Comparative Law on the Authority of the House of Representatives (Indonesia) with the National Parliament (Timor Leste) - Rumiartha, I Nyoman Prabu Buana; Indradewi, Anak Agung Sagung Ngurah; Gomes, Alarico (SASI, 2023)
Introduction: Based on the history of the formation of the state constitutions of Timor Leste and the state of Indonesia, it is interesting to conduct special research on a comparison of the legal powers contained in the constitution of the DPR (Indonesia) and the National Parliament (Timor Leste).Purposes of the Research: The purpose of this study is to explain the legal comparison of the powers granted by the Constitution, in this case the legal comparison of the powers of the House of Representatives (Indonesia) and the National Parliament (Timor Leste).Methods of the Research: This research uses normative research methods and comparative law research methods.Results of the Research: The similarity between the people's representative assembly (Indonesia) and the national parliament (Timor Leste) is that they both have the authority to formulate laws, as well as the similarity of legislative functions, budgetary functions, and oversight functions. The difference lies in the right to elect a general high councilor. In the Indonesian constitution, there is no general ministry high council election. The People's Representative Council does not have the authority to elect and appoint ministers, this is the President's authority as a perrogative right. Meanwhile in Timor Leste, the National Parliament elects the high council of general ministries.